Barriers and facilitators to seek treatment for gynecological morbidity among women from urban slums in Pune, India - Geeta S Pardeshi; Murlidhar P Tambe; Ajay S Chandanwale; Radhika S Sharma; Mitali S Wagh (Wolters Kluwer Medknow Publications, 2017)
Background: The high burden of gynecological morbidity along with poor treatment seeking practices indicate the need to identify barriers and facilitators for treatment seeking. Methods: A community based study using mixed methodology was conducted among women in reproductive age group in slums of Pune city. A pretested semi open ended questionnaire was used to record data on sociodemographic variables, symptoms of gynecological morbidity, domestic violence, autonomy and treatment seeking. Data were analysed using logistic regression analysis. Reponses to in-depth interviews were analysed using grounded theory. Results: Out of the 202 women recruited in the study, 116 (57%) reported symptoms of gynecological morbidity of which 64 (55%) reported to have sought treatment. The factors significantly associated with treatment seeking were: discussing symptoms with husband [p=0.001, OR=6.99 (2.11 - 23.12)]; having a role in decision making for major household purchase [p=0.005; OR=4.36 (1.54-12.32)] and reporting four or more symptoms [p=0.015; OR=4.57 (1.34-15.61)]. In-depth interviews identified barriers and facilitators at individual, family, community and health service levels. Conclusion: There was a high prevalence of self-reported gynaecological morbidity amongst women in urban slums and only half of symptomatic women reported to have sought treatment for their symptoms. Women empowerment, health education and initiatives planned under National Urban Health Mission such as linkages with health care set up through ASHAs and community based groups and appointment of lady medical officers and gynecologists at Urban PHCs will facilitate treatment seeking.